Agro-Ecological Sub-region: A wheel of technology transfer for crop planning - Mandal, C.; Bhattacharyya, T.; Venugopalan, M. V.; Tiwary, P.; Pal, D. K. (Indian Farming, 2015)
In the present study all the information which made the backbone of soil information system has been utilized for generating maps for cotton and soybean crops in BSR and rice and wheat in the IGP to find out various soil factors controlling their performance. For example, in the IGP the selected AESRs represented by thedominant soils producing